Evaluasi supervisi administrasi kurikulum dalam meningkatkan mutu program pendidikan - Mawardi Mawardi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Curriculum is an educational program provided by educational institutions for students. Based on this educational program, students engage in various learning activities, thereby promoting their development and growth in line with the established educational goals. To ensure the effective implementation of the curriculum, evaluation and supervision play crucial roles. Curriculum supervision encompasses all efforts undertaken by supervisors in the form of assistance, guidance, motivational support, and direction aimed at improving teachers' capabilities in instructional practices, which, in turn, enhance students' learning outcomes. The primary objectives of curriculum evaluation and supervision in education are to empower teachers with improved teaching skills. The success of curriculum supervision is evidenced by the improvement in students' learning outcomes. Thus, curriculum evaluation and supervision emphasize guidance and support for teachers to develop professional competencies in implementing educational curricula, leading to better, more effective, and successful educational outcomes